GAMBARAN PEMANFAATAN BUKU KIA PADA IBU HAMIL DI WILAYAH KELURAHAN PALAM - Prihatanti, Nur Rohmah; Hapisah, Hapisah; Rizani, Ahmad; Daiyah, Isrowiyatun; Megawati, Megawati; Ismarini, Novi (Jurnal Ilmiah Maternal, 2023)
ABSTRACT. The Maternal and Child Health Book (KIA Book) is a book that contains health information for mothers, from the time of pregnancy, during childbirth, during the postpartum period and continues to record the health of newborns until the child is 5 years old. The KIA book integrates several health records in the community. The KIA book is useful in improving family and community behavior in maintaining maternal and child health and improving communication between health workers and clients to help families obtain quality and sustainable Maternal and Child Health services. Based on the 2018 Basic Health Research, the results of the analysis showed that 60% of mothers were able to show their KIA book during the examination, as many as 10% could not show their KIA book, and as many as 30% of mothers did not have a KIA book at all. This shows that ownership of the KIA book is still below the service standard target of 100%. The type of research used is descriptive. The research was conducted in Palam Village in May 2023. The research population was pregnant women in the Palam Village area. The sample used was accidental sampling with a total of 13 respondents, all of whom were patients at the Palam auxiliary health center. The research variable is the utilization of the KIA book for pregnant women. The instrument used is a questionnaire. Data analysis using univariate analysis. The results showed that all pregnant women in the Palam Village area had used the KIA book properly (100%). Utilization of the KIA book is very effective in facilitating the improvement of health behavior, continuing care during the antenatal, intranatal and postnatal periods, as well as recording/keeping health records. Keywords: KIA book, Pregnant Women, Children  ABSTRAK. Buku Kesehatan Ibu dan Anak (Buku KIA) adalah buku yang berisi informasi kesehatan untuk ibu, sejak masa hamil, saat melahirkan, masa nifas dan berlanjut untuk mencatat kesehatan bayi baru lahir sampai anak berusia 5 tahun. Buku KIA mengintegrasikan beberapa catatan kesehatan di komunitas. Buku KIA bermanfaat dalam memperbaiki perilaku keluarga dan masyarakat dalam memelihara kesehatan ibu dan anak serta meningkatkan komunikasi antara tenaga kesehatan dan klien untuk membantu keluarga memperoleh pelayanan Kesehatan Ibu dan Anak yang bermutu dan berkesinambungan. Berdasarkan Riset Kesehatan Dasar tahun 2018, hasil analisis menunjukkan bahwa 60 % ibu bisa menunjukkan buku KIA saat pemeriksaan, sebanyak 10 % tidak dapat menunjukkan buku KIA, serta terdapat sebanyak 30% ibu yang sama sekali tidak memiliki buku KIA. Hal ini menunjukkan bahwa kepemilikan buku KIA masih dibawah target standar pelayanan yaitu sebesar 100%. Jenis penelitian yang digunakan adalah deskriptif. Penelitian dilakukan di Kelurahan Palam pada bulan Mei 2023. Populasi penelitian adalah Ibu hamil di wilayah Kelurahan Palam. Sampel yang digunakan adalah accidental sampling dengan jumlah responden 13 orang yang keseluruhan merupakan pasien di Puskesmas Pembantu Palam. Variabel penelitian adalah pemanfaaatan buku KIA pada Ibu hamil. Instrumen yang digunakan adalah dengan kuesioner. Analisa data menggunakan analisis univariat. Didapatkan hasil bahwa Ibu hamil di wilayah Kelurahan Palam seluruhnya telah memanfaatkan buku KIA dengan baik (100 %). Pemanfaatan buku KIA sangat efektif untuk memfasilitasi peningkatan perilaku kesehatan, perawatan yang berkelanjutan selama periode antenatal, intranatal, dan postnatal, serta sebagai rekaman/menyimpan catatan kesehatan. Kata Kunci: Buku KIA, Ibu Hamil, Ana